228 Braf inhibitors, sb590885 and dabrafenib, enhance erk1/2 signalling in cardiomyocytes and promote cardiac hypertrophy. (5th June 2017) - Meijles, Daniel; Hardyman, Michelle; Rostron, Kerry; Fuller, Stephen; Sugden, Peter; Clerk, Angela
Abstract : Purpose: ERK1/2 are phosphorylated and activated by MKK1/2 that are phosphorylated and activated by Raf kinases. ERK1/2 promote cardiomyocyte hypertrophy and is protective, whereas they promote proliferation in cancer cells. Mutations in BRaf are commonly found in cancer, and drugs targeting the enzyme are in clinical use. Of these, the type I inhibitor, SB590885 (SB), binds to the active conformation of BRaf, whilst dabrafenib has no activation state selectivity. Paradoxically, these inhibitors activate ERK1/2 in cancer cells by stimulating the cascade at low concentrations rather than inhibiting it. Our aim is to determine the effects of BRaf inhibitors on the ERK1/2 cascade in cardiomyocytes to establish whether they may activate the pathway in the hearts of patients undergoing cancer therapy. Methods: Rat neonatal cardiomyocytes were exposed to dabrafenib or SB and the effects on activation of MKK1/2 or ERK1/2 examined by immunoblotting with antibodies to phosphorylated (i.e. activated) or total kinases. Raf activities were assayed using GST-MKK1 as a substrate. The effects on myocyte morphology were studied by immunostaining for myofibrillar proteins. Results: Low concentrations of SB (0.1 µM) or dabrafenib (1 µM) enhanced ERK1/2 signalling, with SB having a greater effect than dabrafenib. Thus, cardiomyocytes are primed for paradoxical activation of ERK1/2 by BRaf inhibitors. One explanation for the Raf paradox is that BRaf forms homo or heterodimers with cRaf. Thus, a submaximal concentration of BRaf inhibitor may be sufficient to inhibit only one Raf protein and, since the kinase is locked in an active state, there is activation of the other Raf partner. Consistent with this, 0.1 µM SB increased activities of both BRaf and cRaf, although there was no significant increase in dimerization. High concentrations of SB or dabrafenib (1–10 µM) inhibited basal ERK1/2 activity in cardiomyocytes, but the inhibitory effect was only transient and levels returned to basal within 1 hour. Furthermore, high concentrations of SB activated ERK1/2 over prolonged periods (up to 24 hour). This was associated with an increase in cardiomyocyte size and myofibrillar organisation consistent with low level activation of the pathway promoting cardiomyocyte hypertrophy. In mouse hearts in vivo, dabrafenib and SB590885 enhanced MKK1/2 phosphorylation over 24 hour, and increased hypertrophic ANF and BNP mRNA expression markers, consistent with the cell data. Conclusions: Cardiomyocytes are primed for Raf paradox signalling and BRaf inhibitors such as SB and dabrafenib activate ERK1/2 in cardiomyocytes. Consistent with a role for ERK1/2 in cardiomyocyte hypertrophy, SB increases expression of hypertrophic gene markers and promotes morphological changes associated with hypertrophy.